2015
DOI: 10.1021/acs.jpcb.5b06168
|View full text |Cite
|
Sign up to set email alerts
|

Novel Microwave Thermodynamic Model for Alcohol with Clustering Structure in Nonpolar Solution

Abstract: A solution containing ethanol as polar material and either benzene or n-dodecane as nonpolar solvent was heated by microwave irradiation employing a single-mode resonance microwave device. Although the microwave heating efficiency was expected from the just value of the relative dielectric constant (εr') or relative dielectric loss (εr″) for liquid system, it was revealed that the clustering structure of alcohol molecules expected from the excess parameter such as the excess relative dielectric loss is the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This is evidence of the nonthermal microwave effect of d W because this process does not change the heat energy of the system. In the case of ethanol, molecular order may increase the number of hydrogen bonds between the OH groups because ethanol molecules form clusters in a nonpolar solvents, which induces a lower field chemical shift; that is the opposite direction of conventional thermal heating. In summary, the entropy term is decreased to supply the microwave energy to the system and the entropy term is then subsequently increased because of dielectric loss to dissipate the energy (d Q + d W ) to the system (Figure b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is evidence of the nonthermal microwave effect of d W because this process does not change the heat energy of the system. In the case of ethanol, molecular order may increase the number of hydrogen bonds between the OH groups because ethanol molecules form clusters in a nonpolar solvents, which induces a lower field chemical shift; that is the opposite direction of conventional thermal heating. In summary, the entropy term is decreased to supply the microwave energy to the system and the entropy term is then subsequently increased because of dielectric loss to dissipate the energy (d Q + d W ) to the system (Figure b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The interest in determining dielectric spectra of liquid mixtures resides in studying the dynamics of these systems and identifying possible deviations from the behavior of pure components and their ideal mixtures. The microwave heating efficiency in these types of binary system has been shown to depend significantly on the nonideality of the mixture, where higher heating rates are obtained for compositions at which negative deviations from the ideal solution are observed and intermolecular interactions are weaker . The amount of experimental work in this area is significant and includes systems such as alcohol/water, glycine/water, , DMSO/alcohol, and mixtures of acetone, DMSO, and isopropanol .…”
Section: Introductionmentioning
confidence: 99%
“…14% (MG-A and MG-B in 50 vol.% ethanol); this difference was unlikely due to microwave pulsed irradiation, at least within experimental error. Earlier, we reported that the microwave heating efficiency depends on the state of the mixture, not on the mixing ratio, for a mixed solution of water and alcohol 20 . Therefore, this reaction system is associated with selective heating by microwaves at the cluster level.…”
Section: Resultsmentioning
confidence: 86%